2016
DOI: 10.1016/j.cardfail.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Extended Follow-Up of Patients With Heart Failure Receiving Autonomic Regulation Therapy in the ANTHEM-HF Study

Abstract: Chronic open-loop ART via left- or right-sided VNS continued to be feasible and well-tolerated in patients with HF with reduced EF. Improvements in cardiac function and HF symptoms seen after 6 months of ART were maintained at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 8 publications
1
94
0
Order By: Relevance
“…Patient baseline characteristics have been previously published . Briefly, 87% (51 of 59) were male, and average age was 52 ± 12 (mean ±SD) years.…”
Section: Resultsmentioning
confidence: 99%
“…Patient baseline characteristics have been previously published . Briefly, 87% (51 of 59) were male, and average age was 52 ± 12 (mean ±SD) years.…”
Section: Resultsmentioning
confidence: 99%
“…; De Ferrari, ; Premchand et al . , ) have indicated improvements in ejection fraction and decreases in cardiac size with VNS, the third study reporting neutral effects (Zannad et al . ).…”
Section: Structural and Functional Organization Of The Cardiac Nervoumentioning
confidence: 99%
“…Preliminary data from these trials likewise indicated that therapeutic levels of VNS can be delivered from either the right or left vagus (Premchand et al . , ). To date, two of three reported trials (De Ferrari et al .…”
Section: Structural and Functional Organization Of The Cardiac Nervoumentioning
confidence: 99%
“…The current FDA-approved protocol requires general anesthesia for about 1 h of surgery needed to implant a pulse generator, run subcutaneous wires, and place the stimulation lead around either the left or right cervical vagus nerve. The left vagus nerve is stimulated for treatment of epilepsy and depression because it is thought to have less influence on cardiac rate than the right vagus nerve (Howland, 2014), but stimulation of either right or left vagus nerve appears to be safe and effective in patients with chronic heart failure (Premchand et al, 2014; Premchand et al, 2016). Stimulation of the vagus is phasic ( e.g.…”
Section: Clinical Studies and Trialsmentioning
confidence: 99%